Blood borne infections in sport: risks of transmission, methods of prevention, and recommendations for hepatitis B vaccination - Kordi, R.; Wallace, W. A. (British Journal of Sports Medicine, 2004)
Athletes are at risk of blood borne infections through bleeding injuries or injection of drugs with contaminated syringes. Prevention should focus on reducing non-sport associated risky behaviour, as well as dealing appropriately with bleeding injuries. The risk of transmission of hepatitis B virus is particularly high in athletes in contact and collision sports, those who live in or travel to endemic regions, injecting drug abusers, and those who practice first aid when there is no healthcare practitioner available. It is recommended that such athletes, and also adolescent athletes, should be vaccinated against the virus as a routine.